Paleotectonic and paleogeographic criteria for forecasting hydrocarbon accumulations in the water area of the Sakhalin shelf - V. Yu. Kerimov; D. A. Kisler; A. K. Shatyrov; E. Z. Idiyatullina (Известия высших учебных заведений: Геология и разведка)
Background. The article considers paleotectonic and paleogeographic criteria for forecasting hydrocarbon accumulations and determining the sites of priority exploration on the Sakhalin shelf.Aim. To determine the priority objects of geological exploration on the Sakhalin shelf based on paleotectonic and paleogeographic criteria.Materials and methods. Generalization and statistical processing of available data, fieldwork materials, reference literature, and scientific publications. Modeling of the tectonic evolution of the Cenozoic sedimentary basin in the studied section of the Sakhalin shelf and its individual sections. The formation and evolution of hydrocarbon systems in the waters of the Sakhalin shelf occurred in the process of geodynamic evolution of the West Okhotsk megabasin covering modern Sakhalin and the adjacent water area. The PetroMod (Schlumberger) and Qgis software packages were used.Results. The developed paleotectonic and paleogeographic criteria are suitable for both determining the sites of priority exploration and developing appropriate recommendations. Schemes with the allocation of areas that meet the developed criteria were constructed. For all three license areas, the stage of prospecting and evaluation of the oil and gas deposits is required, along with the completion of the exploration and production stage at already discovered fields. Within the license areas, the most promising structures were identified and boreholes were outlined.